2011
DOI: 10.1039/c1cp20559e
|View full text |Cite
|
Sign up to set email alerts
|

The influence of polarizability on the dielectric spectrum of the ionic liquid 1-ethyl-3-methylimidazolium triflate

Abstract: This work reports for the first time the computational, frequency-dependent dielectric spectrum of the polarizable molecular ionic liquid 1-ethyl-3-methylimidazolium triflate as well as its experimental analogue. In the frequency range from 500 MHz up to 20 GHz the agreement between the computational and the experimental spectrum is quantitative. For higher frequencies up to 10 THz the agreement is still remarkably good. The experimental asymptotic limit e N is 2.3. The difference in the computational value of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
66
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(69 citation statements)
references
References 75 publications
3
66
0
Order By: Relevance
“…5 However, the high-frequency mode is just a formal description of the significant contributions from librations and intermolecular vibrations dominating the far-infrared region. 5,8,25 Consistent with the bimodal character of the spectra at intermediate concentrations ( Fig. 2) and similar to IL + dichloromethane mixtures 25 all mixture spectra could be well fitted with the CC+D model (Fig.…”
Section: Dielectric Datasupporting
confidence: 75%
“…5 However, the high-frequency mode is just a formal description of the significant contributions from librations and intermolecular vibrations dominating the far-infrared region. 5,8,25 Consistent with the bimodal character of the spectra at intermediate concentrations ( Fig. 2) and similar to IL + dichloromethane mixtures 25 all mixture spectra could be well fitted with the CC+D model (Fig.…”
Section: Dielectric Datasupporting
confidence: 75%
“…Simulations suggest that at least for imidazolium RTILs the α relaxation is not a pure rotational motion but also significantly involves translations of cations and anions [47]. This might explain why the effective volumes of rotation derived from a Stoke-Einstein-Debye analysis of τ α yields values incompatible with cation reorientation via rotational diffusion [35].…”
Section: α Relaxationmentioning
confidence: 99%
“…This mainly translational mode is associated with the rattling of molecules in their cage of surrounding neighbors superimposed on the formation and decay of these cages. An argument from MD simulations if favor of such an assignment also for RTILs is provided by the strong collective translational contributions (interionic vibrations) to the simulated dielectric spectrum in this frequency range [47,53]. 18.2 ± 1.…”
Section: Short-time Dynamicsmentioning
confidence: 99%
“…Note that this empirical decomposition of the dielectric spectra has to be taken with a grain of salt as computer simulations of Schröder et al have clearly shown that at least for imidazolium-based ionic liquids and their mixtures with water rotational and translational modes of all components stretch over large frequency ranges and strongly overlap. [39][40][41] However, as long as quantitative agreement between experimental and simulated dielectric spectra cannot be routinely achieved empirical decompositions, like the present CC + D or HN i + D models, have to be used.…”
Section: Choice Of Fit Modelmentioning
confidence: 99%